Oral health of the population, a priority in all policies - Estela de los Ángeles Gispert Abreu; Jorge Luis Bécquer Águila (Editorial Ciencias Médicas, 2015)
The oral health of populations should be a priority for states, governments, sectors of society, the economy and the population itself in different contexts; but the reality is that this aspect of health continues to be relegated in many areas where it is considered primarily an aesthetic-cosmetic issue, alien to public health and therefore, have been marginalized from public policies aimed at protecting health. The actions destined to its integral development in terms of promotion and social participation are manifested as weak, disintegrated and ephemeral. It is committed to the incorporation of oral health to the "Health in all policies" approach, based mainly on human rights and social justice, according to the Declaration of Helsinki. Taking oral health into account in all policies would have an impact on the promotion of synergies (within and outside the health sector), for the choice of priorities, decision-making, planning, execution, control of policies and actions for the population's oral health , which should be supported by governments and states. However, within the framework of health in all policies at the global and regional levels, experiences derived from case studies that demonstrate their impact on oral health are usually not taken into account. This conspires against the establishment of an action plan with strategic goals and objectives, comprehensive and integrated from the local to the regional and global level, and leads to oral health problems that extend and worsen. Although there is no continuous statistical system, it has been recognized that:     - the world population is affected in 90% by some of the oral health problems, mainly (dental caries, periodontal diseases and malocclusions); however, only 60% have access to health services.     - Between 60% and 90% of school children worldwide have dental caries and dentistry is considered to be the main cause of absenteeism in schools in many countries.     - Oral cancer, the eighth type of cancer in the world and the most expensive to treat, has an incidence of between 1 and 10 cases over 100,000 in most countries.     - Severe periodontal diseases affect an estimated between 5% and 20% of adults of mature age.     - Oral diseases can cause periodontal complications that are more common in older people.     - The prevalence of dental caries, periodontal diseases and oral cancer are associated with social determinants of health such as poverty, inequalities, access to education, sources of work, drinking water and health services, among others.     - risk factors such as smoking, high sugar intake and deficient in vegetables contribute to several chronic diseases, including oral diseases.     - oral health impacts on general health and affects self-esteem, social interaction; also causes alterations of several essential functions for life.     - Oral health care starts with good brushing habits and regular exams; however the price of toothbrushes, and supplements to make it easier and more pleasant and effective tends to be high in countries where the population has low income; likewise, access to services in countries where care is not free or in which public health covers only very basic benefits is also limited by high costs.     - there are more than one million dentists worldwide that with modern dental treatments can restore almost all functions, although in the poorest and most needy regions of the world the figure is very low. The analysis of the global situation with oral health shows that for the construction of population oral health, greater access to health services is needed with promotional-preventive orientation and capital with social relevance extended beyond the borders of the health sector. This justifies the importance of its approach through intersectoral public policies, and of evaluating the short, medium and long term impact of these policies on social determinants, risk factors and oral health indicators.